APPLICATION OF CHARACTER EDUCATION IN ESTABLISHING ISLAMIC BEHAVIOR OF STATE JUNIOR HIGH SCHOOL 2 (SMPN 2) STUDENTS IN KEBOMAS GRESIK - Nabil Abu Baka; Hasan Basri; Mohammad Ahyan Yusuf Sya’bani (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2021)
This study aims at finding character education in establishing Islamic behavior of SMPN 2 Kebomas Gresik, explaining implementation of character education, and understanding supportive and inhibitive factors of character education implementation in establishing daily character students. The aim gives point of student character establishment in character education; for example, some classical books, such as, Taisirul Kholak, Taklim Muta’alim, Akhlak Lilbanin, Bidayatul Bidayah and other tasawuf character books. Teaching materials associated with sleeping character were taken from Taisirul Kholak, Bidayahtul Hidayah, and Akhlak Lilbanin. Those associated with cleanse were taken from Taisir, Bidayah and some Fiqh books associated with cleanse, and others up to character of environment. Some sufficiently effective methods  in daily character education of students are made by habituation, exemplification, disciplines, and sometimes reward and punishment. Supportive factors of student character establishment are religious learning activities, adequate facilities, enthusiasm of students and teachers, scope confortable and far from crowdedness, and code of conduct to obey. In addition to the supportive factors, there are inhibitive factors, such as, violation by student and effect outside school.Keywords: character education, Islamic behavior.